Estimating the reduced benefit of infant-directed speech in cochlear implant-related speech processing. (October 2021) - Arjmandi, Meisam; Houston, Derek; Wang, Yuanyuan; Dilley, Laura
Highlights: Simulated cochlear-implant processing reveals a significant reduction in the acoustic distinctiveness between IDS and ADS. The estimated intelligibility benefit of IDS over ADS is greatly reduced due to cochlear-implant processing. Cochlear-implant processing potentially weakens the link between attending to IDS and improved language learning. Abstract: Caregivers modify their speech when talking to infants, a specific type of speech known as infant-directed speech (IDS). This speaking style facilitates language learning compared to adult-directed speech (ADS) in infants with normal hearing (NH). While infants with NH and those with cochlear implants (CIs) prefer listening to IDS over ADS, it is yet unknown how CI processing may affect the acoustic distinctiveness between ADS and IDS, as well as the degree of intelligibility of these. This study analyzed speech of seven female adult talkers to model the effects of simulated CI processing on (1) acoustic distinctiveness between ADS and IDS, (2) estimates of intelligibility of caregivers' speech in ADS and IDS, and (3) individual differences in caregivers' ADS-to-IDS modification and estimated speech intelligibility. Results suggest that CI processing is substantially detrimental to the acoustic distinctiveness between ADS and IDS, as well as to the intelligibility benefit derived from ADS-to-IDS modifications. Moreover, the observed variability across individual talkers in acoustic implementation of ADS-to-IDS modification and the estimated speech intelligibility was significantly reduced due to CI processing. The findings are discussed in the context of the link between IDS and language learning in infants with CIs.